Characteristics of CoPc/CdS hybrid diode device - Caliskan, Murat; Yesilkaya, Serco Serkis; Canlica, Mevlude (INDIAN ACAD SCIENCES, 2015)
CdS/CoPc hybrid heterojunctions were fabricated and characterized. CdS films were deposited by the spray pyrolysis technique on indium tin oxide (ITO)-coated glass substrates and CoPc films coated on CdS by chemical precipitation. Ag contact metal deposited on CoPc by e-beam evaporation and glass/ITO/CdS/CoPc/Ag structures were fabricated. Rectification ratio, ideality factor, barrier height and junction parameters of the devices were determined. It is shown that device has diode characteristics with the ideality factor (n) of 4.8, rectification ratio of 4.5 and the built-in voltage (V-b) of 0.48 V. Absorption energy for CoPc was found as 1.57 eV. The results encourage utilizing CoPc as absorber organic material for solar cells.
Keywords: Asymmetric Co(II)phthalocyanine; CdS; organic; thin film; diode; THIN-FILMS; DEPOSITED CDS; PHTHALOCYANINE; CELLS; Materials Science